2017
DOI: 10.1136/annrheumdis-2016-210882
|View full text |Cite
|
Sign up to set email alerts
|

Enteric-coated mycophenolate sodium versus azathioprine in patients with active systemic lupus erythematosus: a randomised clinical trial

Abstract: NCT01112215; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 32 publications
2
31
0
4
Order By: Relevance
“…The previous analysis of our cohort found that, if >50% of the follow‐up time satisfied LLDAS, there was a 50% reduction in later organ damage . Furthermore, LLDAS has now been found to be a meaningful and discriminative end point in both primary and post hoc analyses of several SLE randomized clinical trials .
The achievability of lupus low disease activity state (LLDAS) in both African Americans and Caucasian patients was demonstrated, supporting the validity of LLDAS in multiple ethnicities. African American patients with systemic lupus erythematosus (SLE) were found to take longer to achieve LLDAS. These findings point to the need to include African American patients with SLE in both clinical and pharmaceutical research, because we cannot generalize from studies from Europe and Asia.
…”
Section: Introductionsupporting
confidence: 58%
“…The previous analysis of our cohort found that, if >50% of the follow‐up time satisfied LLDAS, there was a 50% reduction in later organ damage . Furthermore, LLDAS has now been found to be a meaningful and discriminative end point in both primary and post hoc analyses of several SLE randomized clinical trials .
The achievability of lupus low disease activity state (LLDAS) in both African Americans and Caucasian patients was demonstrated, supporting the validity of LLDAS in multiple ethnicities. African American patients with systemic lupus erythematosus (SLE) were found to take longer to achieve LLDAS. These findings point to the need to include African American patients with SLE in both clinical and pharmaceutical research, because we cannot generalize from studies from Europe and Asia.
…”
Section: Introductionsupporting
confidence: 58%
“…Mycophenolate mofetil (MMF) is a potent immunosuppressant with efficacy in renal and non-renal lupus (although not in neuropsychiatric disease) 51–53. In a recent randomised, open-label trial in extrarenal SLE, enteric-coated mycophenolate sodium (EC-MPS) was superior to AZA in achieving remission and reducing flares 54. However, its teratogenic potential (needs to be discontinued at least 6 weeks before conceiving), along with its higher cost compared with AZA or MTX, poses a limitation towards universal recommendation in women of reproductive age with non-renal manifestations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, rates of LLDAS attainment were demonstrated to differentiate treatments in a trial comparing azathioprine and mycophenolate in nonrenal SLE. 9 Utility of a novel endpoint such as LLDAS in trials of novel therapies requires it to be attainable and to align with existing response measures, but also to offer additional information, and to allow for discrimination between active treatment and placebo. Here, we present a post-hoc analysis of a large Phase IIb SLE RCT dataset and demonstrate LLDAS utility.…”
Section: Introductionmentioning
confidence: 99%